Concurrent Phacoemulsification and Encircling for Hypotony Maculopathy after Blunt Trauma. (12th May 2020) - Baba, Takayuki; Yokouchi, Hirotaka; Yamamoto, Shuichi
Abstract : A 37-year-old Japanese man had his right eye hit by a fist. His right eye developed hypotony maculopathy and secondary cataract, and his visual acuity decreased to 20/200 with an intraocular pressure of 4 mmHg. He underwent phacoemulsification and aspiration, implantation of the intraocular lens, and encircling with a silicone tire. His visual acuity improved to 20/20 and stable for more than one year postoperatively. The intraocular pressure in his right eye increased to 12 mmHg, and maculopathy was resolved entirely. It was suggested that an encircling buckle obstructed the uveoscleral outflow through the cyclodialysis and increased intraocular pressure. Concurrent cataract surgery and encircling was sufficient to improve the vision.